Extended electron transfer and the Frumkin correction - Gavaghan, D; Feldberg, S (2000)
It is now well established that the rate constant for electron transfer between a metal electrode and a given redox moiety (at distance x from the electrode) decays according to exp[ - betax]; values of beta are of the order of 10(8) cm(-1) and depend primarily upon the nature of the intervening medium. The present work demonstrates how this 'extended' electron transfer can modify the Frumkin correction for diffuse layer effects in the measurement of heterogeneous rate constants. We quantify the effect of this 'extended' electron transfer by comparing the electron transfer rate constants deduce